A Violin Recital With Program Notes And Theoretical Analysis - Gail, Katherine A. (Kansas State University, 2002)
This report is written in conjunction with a Master of Music violin recital, performed in All Faiths Chapel on Monday March 25, 2002. It contains biographical information about each composer presented on the recital. It also includes theoretical analysis and historical background about each of the performed works. Chapter one begins with a basic biography of Ludwig van Beethoven. Historical significance and a theoretical analysis of the Sonata No. I in D Major for Violin and Piano, Opus 12 are also included. Some thoughts about the importance that these sonatas had on the evolution of the duo-sonata style are presented. Chapter two deals with American composer Alan Vaness Scott Hovhaness, a brief explanation of his life and compositional techniques, and analysis of the Khirgiz Suite for Violin and Piano, Opus 7 3. Johann Sebastian Bach is discussed in chapter three. His life and the importance of his works for violin are introduced first. An analysis of his Sonata No. I in b minor for Harpsichord and Violin, BWV I 014, including important contrapuntal techniques and performance-practice suggestions, are subsequently introduced. The final chapter deals with Cesar Franck's Sonata in A Major for Violin and Piano. Discussions include the importance of this cyclic work and a brief biography about Eugene Y saye - the violinist for whom the work was written. Questions about Franck's nationality and the influence that his choir positions - including his position as organist - held upon his compositional style are also explained.